Intra-industry trade in horizontally and vertically differentiated agrifood products between Hungary and the EU - Imre Ferto; Lionel J. Hubbard (Hungarian Academy of Sciences, Institute of Economics, 2002)
Intra-industry trade in agri-food products between Hungary and the EU is shown to be low and dominated by vertically rather than horizontally differentiated products, suggesting higher economic adjustment costs. Following recent empirical studies, we then test econometrically for the determinants of this trade using different measures of horizontal and vertical trade, and employing an array of popular explanatory variables. Results suggest that separating the measure of intra-industry trade into vertical and horizontal provides for better estimation and supports the contention that the determinants may differ by type of trade. In the regression analysis, the level of intra-industry trade is found to serve as a better dependent variable than the degree or share of intra-industry trade.
Keywords: 330